A comparative analysis of the competition strategy of seaports under carbon emission constraints. (10th August 2021) - Gan, Mi; Li, Dandan; Wang, Jiawei; Jiankui Zhang; Huang, Qinglan
Abstract: The development of ports is essential to the competitiveness of cities. Harbor cities in China have put much effort into expanding the business of their ports, ignoring the overlapping of hinterland markets with other ports. Excess resources expended by ports may intensify regional environmental issues, such as carbon emissions. Motivated by the emissions reduction targets proposed by the International Maritime Organization and the urgent need for the development of green and sustainable ports, the Chinese government is trying to draft a carbon constraint policy to prevent the disorderly development of ports. It is thus necessary to study competition strategies under the context of carbon emission constraints. In this paper, the improved Hotelling model is used to describe the competitive relationship between ports. Then, three competition scenarios of the seaports under no carbon emissions policy, a carbon emission cap policy, and a carbon cap-and-trade policy are examined to analyze the effects of carbon emissions policy on port service prices, demand for goods, maximum profits, and social welfare. The results show that (1) from the perspective of port managers, only when government-defined carbon emission limits are lower than the critical value, the carbon cap policy is binding on port competition; when it comes to the cap-and-trade policy, government-defined carbon emission limits only affect profits. (2) From the government's perspective, the cap-and-trade policy maximizes social welfare more than the other policies regardless of the value of government-defined carbon emission limits.